The Potential of Indonesian Honey to Change the Lipid Profiles of Individuals with Central Obesity - Jayadi, Yusmaindah; Thaha, Abdul Razak; Hadju, Veni; Bukhari, Agussalim; Dewi, Nikmah Utami; Bohari (Pakistan Journal of Nutrition, 2019)
Background and Objective: Honey has the ability to improve lipid profiles and influence cholesterol and triglyceride levels in individual with central obesity. Central obesity can be defined as visceral fat accumulation in the upper part of the body. This study was conducted to analyze the effect of the administration of 70 g of honey per day for two months on lipid profiles in patients with central obesity. Materials and Methods: This study had a quasi-experimental design, with a non randomized group with pre- and post tests. The sample population consisted of 25 subjects who received the intervention and 25 control subjects. The intervention group was administered honey and provided obesity education. The control group only received obesity education. The 70 g of honey was administered in 250 mL of water each day for 60 days, while obesity education was provided three times within the study period. Total cholesterol, LDL, HDL and triglyceride levels were assessed in both the intervention and control groups as outcomes. The Wilcoxon and Mann-Whitney tests were used to analyze the data. Results: There were no significant differences between the intervention group and the control group in terms of age, BMI, waist circumference and lipid profile before the intervention (p>0.05). The main effects in the intervention group were reduced levels of total cholesterol (2.25±9.7, p = 0.33) and LDL (1.85±13.2, p = 0.4). The total amount of honey consumed, which was ≥4000 g in the intervention group, showed that total cholesterol (p = 0.00), LDL (p = 0.00) and HDL (p = 0.00) levels differed significantly before and after treatment, with decreases of 6.96±7.26, 8.87±9.79 and 10.9±8.97, respectively. A non-significant difference was found in the triglyceride level of 14.9±27.57 (p = 0.36). Conclusion: The administration of honey produced in Indonesia significantly reduced the levels of total cholesterol, LDL and HDL in individuals with central obesity; the level of triglyceride was not affected.